O-005 Multicenter experience utilizing CT perfusion guided patient selection for intra-arterial thrombectomy. (4th July 2012) - Turk, A; Frei, D; Fargen, K; Magarik, J; Chaudry, I; Huddle, D; Mocco, J; Bellon, R; Turner, R
Abstract : Background: Traditional treatment in acute ischemic stroke is based on time criteria when administering intravenous and intra-arterial therapies. However recent evidence suggests that image based criteria may be useful for selecting patients for intra-arterial interventions. We investigated CT perfusion (CTP) based criteria, regardless of time from symptom onset, in patient selection for intra-arterial treatment of ischemic stroke. Methods: We retrospectively assessed ischemic stroke patients who presented to the Medical University of South Carolina, the University of Florida Medical Center, and Swedish Medical Center in Denver, over the last 4 years, with a National Institute of Health Stroke Scale (NIHSS) score of ≥8, regardless of time from symptom onset. CTP maps were qualitatively assessed for presence of penumbra and infarction. Selected patients underwent mechanical thrombectomy of their occlusion, nearly all using the Penumbra Aspiration System. We then recorded functional outcome using the modified Rankin scale at 90 days or closest follow-up to 90 days. We will continue to update this data until time of presentation. Results: 271 patients were included in the study. The median time from symptom onset to groin access in all patients was 6.0 h and patients were therefore divided into two groups based on that time point. Overall, 52 patients (19.9%) had bleeding complications, including subarachnoid hemorrhage, parenchymal hemorrhage and intraventricular hemorrhage, but only 12% were symptomatic. After CTP based selection patients were divided into two groups for analysis: ≤6 h and >6 h from symptom onset to endovascular procedure. We found no significant difference in functional outcome between the two groups 43% and 43.2% that achieved 90-day mRS ≤2, respectively (p=1.0), and 60.5% vs 55.3% (p=0.8) that achieved 90-day mRS ≤3, respectively. We found no difference in the rate of intracranial hemorrhage between the two groups 21% vs 17.3% (p=0.704), respectively. Conclusion: Our study demonstrated similar rates of good functional outcome and intracranial hemorrhage in ischemic stroke patients when endovascular treatment was performed based on CTP selection rather than time-guided selection. Our findings suggest that endovascular reperfusion in ischemic stroke may be effective and safe when imaging based paradigms are followed, and may allow patient selection not solely based on time from symptom onset. Competing interests: A Turk: Stryker, Pulsar Vascular. Penumbra, Stryker, Siemens, Codman, Microvention, eV3, NFocus, Pulsar Vascular, Lazarus Effect. D Frei: Penumbra. K Fargen: None. J Magarik: None. I Chaudry: Penumbra. D Huddle: None. J Mocco: Penumbra, Stryker. Penumbra, Stryker. R Bellon: None. R Turner: Penumbra.